Protective effects of chlorine dioxide solution on postharvest pericarp browning and oxidative damage of longan fruit - S. Intarasit (2018)
Occurrence of postharvest pericarp browning and rapid decay limits the postharvest storage life of longan fruit. The purpose of this study was to evaluate the efficiency of aqueous chlorine dioxide (ClO2) in reducing pericarp browning related to oxidative membrane damage in 'Daw' longan fruit. Longan fruits were dipped in 0 (control), 25, 50 and 100 mg L-1 ClO2 solutions for 10 min. After dipping, the fruits were packed in cardboard boxes and stored at 25±1°C with a relative humidity of 82±5% for 5 days. The results showed that the fruits treated with ClO2 solutions had lower browning index (BI) than that of the control group during storage for 4 days, although no significant difference was found on day 5. Fruits treated with ClO2 solutions maintained BI of below 3 for 2-3 days depending on concentrations, whereas the control maintained this index for only one day. Reactive oxygen species (ROS) levels, including hydrogen peroxide (H2O2) and hydroxyl radical (OH•), and membrane damage, as measured by electrolyte leakage (EL), lipoxygenase (LOX) activity, malondialdehyde (MDA) and conjugated diene (CD) contents in pericarp were significantly lower in the ClO2-treated group than those in the control group and correlated with BI. ClO2 solution at concentrations of 50 and 100 mg L-1 was the most effective in reducing pericarp browning and oxidative damage. Results of the study indicated that aqueous ClO2 could reduce ROS free radical and oxidative membrane damage, resulting in reducing in pericarp browning of harvested longan fruits during storage for 4 days.